RANCANG BANGUN SISTEM MONITORING STASIUN PENGISIAN LISTRIK UMUM (SPLU) HYBRID BERBASIS IOT DI SMKN 2 KOTA BEKASI - Abdurrahman, Naufal; Jaenul, Ariep; Vresdian, Devan Junesco (Program Vokasi-Universitas Negeri Gorontalo, 2024)
This research is motivated by the development of electric vehicles in Indonesia which is regulated in Presidential Regulation Number 55 of 2019 which encourages the use of electric vehicles. Therefore, the development of electric vehicles began to increase every year. Along with the development of electric vehicles, it must also be followed by the development of charging stations. This research focuses more on developing a Hybrid public electric charging station (SPLU) monitoring system to create a Hybrid SPLU monitoring system that can be accessed easily anytime and anywhere in real-time and is IoT-based. For the Hybrid SPLU monitoring system to work well, the data results from sensor readings can be monitored in real-time and IoT-based. Then the data from this study has been compared (calibration) with existing measuring instruments with the average error of each sensor being no more than 5% and the Mean Absolute Percentage Error (MAPE) not more than 10%. From the existing provisions, if the MAPE value is <10%, the data can be said to be very accurate. So it can be concluded that this research can be said to be successful because it has fulfilled the initial objectives of this research.